2009
DOI: 10.1186/1475-2875-8-246
|View full text |Cite
|
Sign up to set email alerts
|

Malaria treatment perceptions, practices and influences on provider behaviour: comparing hospitals and non-hospitals in south-east Nigeria

Abstract: BackgroundPeople seek treatment for malaria from a wide range of providers ranging from itinerant drug sellers to hospitals. However, there are lots of problems with treatment provision. Hence, factors influencing treatment provision in hospitals and non-hospitals require further investigation in order to remedy the situation.ObjectivesTo examine the knowledge, pattern of treatment provision and factors influencing the behaviour of hospitals and non-hospitals in the treatment of malaria, so as to identify loci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 12 publications
11
32
0
Order By: Relevance
“…[17] Similarly, a cross-sectional study of malaria treatment practices and perceptions in Southeast Nigeria also observed good knowledge among PHC workers. [18] This good knowledge did not show in the management practices of the PHC worker as has been observed by other researchers. [19] In this study mean score for malaria case management of under-fives was rather low with minimal changes recorded at post-intervention.…”
Section: Knowledge Diagnosis and Treatment Of Malariasupporting
confidence: 63%
See 1 more Smart Citation
“…[17] Similarly, a cross-sectional study of malaria treatment practices and perceptions in Southeast Nigeria also observed good knowledge among PHC workers. [18] This good knowledge did not show in the management practices of the PHC worker as has been observed by other researchers. [19] In this study mean score for malaria case management of under-fives was rather low with minimal changes recorded at post-intervention.…”
Section: Knowledge Diagnosis and Treatment Of Malariasupporting
confidence: 63%
“…This finding is consistent with other findings on healthcare workers treatment patterns. [18,24] In the review of case management among PHC workers in Sokoto, 86.2% of respondents commonly prescribed CQ as the first line drug and 4.6% prescribed ACT's with wrong drug dosages in 63.6% of the time. [24] In this study dosages were wrong in 67.3% of cases.…”
Section: Knowledge Diagnosis and Treatment Of Malariamentioning
confidence: 99%
“…This might be due to patient's inability to afford malaria parasite diagnostic test which is quite expensive. The results of the present study are in line with the study conducted in Nigeria where the use of presumptive malaria diagnosis without laboratory support, was a common diagnostic procedure for malaria and inclined to poor quality of malaria diagnosis and treatment [14]. However, it was observed that prescribing of anti-malarial drugs after laboratory confirmation only decreased the total number of malaria prescriptions significantly in Malawi [15].…”
Section: Discussionsupporting
confidence: 79%
“…Social relationships are often based on a perceived or real demand from patients for antimalarials (Chandler et al, 2008b;Onwujekwe et al, 2009) as well as habitual practice built on observation and expectations from colleagues within communities of practice (Chandler et al, 2008a;Chandler et al, 2010). Undertaking qualitative studies to understand local conceptualisations of malaria treatment and diagnosis is essential in order to design supporting interventions for the introduction of new technologies such as RDTs in different settings.…”
Section: Introductionmentioning
confidence: 99%